2013
DOI: 10.1155/2013/273052
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solutions for Steady Heat Transfer in Longitudinal Fins with Temperature-Dependent Properties

Abstract: Explicit analytical expressions for the temperature profile, fin efficiency, and heat flux in a longitudinal fin are derived. Here, thermal conductivity and heat transfer coefficient depend on the temperature. The differential transform method (DTM) is employed to construct the analytical (series) solutions. Thermal conductivity is considered to be given by the power law in one case and by the linear function of temperature in the other, whereas heat transfer coefficient is only given by the power law. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 31 publications
(45 reference statements)
0
31
0
Order By: Relevance
“…From Figure , we note the temperature θ increases when increasing x (in other words, the temperature increases when approaching from heat source). Remark When β = n , Equations and become θ=θ0Cosh11+nM1+nxθ0=Cosh11+nM1+n. From , we obtain θ=()Cosh()M1+n0.3emxCosh()M1+n11+n. Equation is obtained in , used in , and obtained as a special case when n=43 in .…”
Section: Numerical Examplementioning
confidence: 89%
See 3 more Smart Citations
“…From Figure , we note the temperature θ increases when increasing x (in other words, the temperature increases when approaching from heat source). Remark When β = n , Equations and become θ=θ0Cosh11+nM1+nxθ0=Cosh11+nM1+n. From , we obtain θ=()Cosh()M1+n0.3emxCosh()M1+n11+n. Equation is obtained in , used in , and obtained as a special case when n=43 in .…”
Section: Numerical Examplementioning
confidence: 89%
“…The steady rate of heat transfer from the entire fin Q f i n can be determined from Fourier's law of heat conduction Qfin=AcK(T)dTdX|X=L. The dimensionless heat transfer rate Q is defined by Q=QfinAcKb(TbTa)/L=AcK(T)dTdX|X=LAcKb(TbTa)/L. Using , Equation becomes Q=θβdx|x=1. From and , when x = 1, we obtain Q=θ(1). Substituting Equation into Equation , we obtain θ=2M2+n+βθβθ2+n+βθ02+n+β. …”
Section: Heat Fluxmentioning
confidence: 99%
See 2 more Smart Citations
“…A brief review of the relevant literature published before 2011 can be found in our previous paper [20]. Research achievements in recent years include nonlinear steady heat conduction analysis for a convective n [21], convective-radiative ns of porous material [22], convective-radiative moving ns (or plates) [23][24][25], a Tshaped n [26] and variable thickness ns [27][28][29], and nonlinear transient heat conduction analysis for variable thickness ns [30]. Recently, the range of application of the DTM has been extended to the analysis of heat conduction in nonhomogeneous bodies [31,32] and phase-change problems [33,34].…”
Section: Introductionmentioning
confidence: 99%